Do I Really Need to Go and See Somebody? Black Women's Perceptions of Help-Seeking for Depression. (May 2020) - Nelson, Tamara; Shahid, Naysha N.; Cardemil, Esteban V.
Black women are among the most undertreated groups for depression in the United States. Few studies have addressed perceptions of help-seeking for depression among Black women. In this study, we interviewed 30 Black women and explored the help-seeking process for depression vis-a-vis social constructivism, intersectionality theory, and the Strong Black Woman (SBW) role, a gendered and racialized role consisting of adherence to strength through independence, emotion regulation, and caretaking. Qualitative analysis revealed that despite positive attitudes toward help-seeking, many participants declined or hesitated to seek treatment. We identified three themes that informed the help-seeking process: (a) You should see somebody; I just would not; (b) Do I really need to go and see somebody; and (c) Self-care despite what others may say. With regard to the influence of the SBW role, we also identified three themes: (a) Masking or ignoring pain, (b) Inability to ask for help, and (c) Lack of self-care. Our findings emphasized the importance of considering how the SBW role may be associated with help-seeking for depression among Black women.